Epidemiologic Analysis of Onychomycosis in the San Diego Pediatric Population. Issue 1 (4th October 2016) - Totri, Christine R.; Feldstein, Stephanie; Admani, Shehla; Friedlander, Sheila F.; Eichenfield, Lawrence F.
Abstract: Background: Onychomycosis (OM) is thought to be a rare disease in children, although there are few epidemiologic studies. Methods: This 3‐year retrospective case series of nearly 400 children seen at Rady Children's Hospital–San Diego (RCHSD) describes the characteristics of OM found in this pediatric population. Results: From 2011 to 2013, the Pediatric and Adolescent Dermatology Clinic at RCHSD saw a total of 36, 634 unique patients, of whom 433 were unique patients with OM. Thirty‐four patients met exclusion criteria, leaving 399 (1.1%) with a diagnosis of OM by a pediatric dermatologist. Nail cultures were obtained in 242 cases (60.7%), 116 (48.0%) of which were positive. Trichophyton rubrum was the most commonly isolated pathogen, responsible for 106 cases (91.3%) of positive cultures in the cohort. Conclusions: Our study provides important regional information regarding epidemiologic data in pediatric onychomycosis, highlighting the diagnostic methods most commonly used and the pathogens most frequently encountered in our practice.